EMT-related cell-matrix interactions are linked to states of cell unjamming in cancer spheroid invasion - Anouk van der Net; Zaid Rahman; Ankur D. Bordoloi; Iain Muntz; Peter ten Dijke; Pouyan E. Boukany; Gijsje H. Koenderink (iScience)
Summary: Epithelial-to-mesenchymal transitions (EMT) and unjamming transitions provide two distinct pathways for cancer cells to become invasive, but it is still unclear to what extent these pathways are connected. Here, we addressed this question by performing 3D spheroid invasion assays on epithelial-like (A549) and mesenchymal-like (MV3) cancer cell lines in collagen-based hydrogels, where we varied both the invasive character of the cells and matrix porosity. We found that the onset time of invasion was correlated with the matrix porosity and vimentin levels, while the spheroid expansion rate correlated with MMP1 levels. Spheroids displayed solid-like (non-invasive) states in small-pore hydrogels and fluid-like (strand-based) or gas-like (disseminating cells) states in large-pore hydrogels or for mesenchymal-like cells. Our findings are consistent with different unjamming states as a function of cell motility and matrix confinement predicted in recent models for cancer invasion, but show that cell motility and matrix confinement are coupled via EMT-related matrix degradation.